2000
DOI: 10.1017/s0033291799001567
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI of the hippocampus and amygdala in severe depression

Abstract: This quantitative MRI study provides support for a possible association between structural and biochemical substrates and severe drug-resistant major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
165
4
13

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(196 citation statements)
references
References 37 publications
(52 reference statements)
14
165
4
13
Order By: Relevance
“…In addition, reduction in the expression of endogenous BDNF has been shown to potentiate seizures induced by hippocampal kindling (Reibel et al 2000). The current work thus raises the possibility that reductions in hippocampal BDNF mRNA induced by uncondititioned stress or by re-exposure to cues previously paired with stress may be involved in the pathophysiology of hippocampus-dependent memory disturbances or decreases in hippocampal volume observed in stress-sensitive psychiatric disorders such as PTSD (Bremner et al 1995;Stein et al 1997;Gurvits et al 1996;Bremner et al 1997) and depression (Mervaala et al 2000;Vakili et al 2000). This also raises the possibility that unconditioned or psychological stress may facilitate the progression of dementing disorders such as Alzheimer's disease in which decreases in hippocampal BDNF levels (Hock et al 2000) and hippocampal volume (Laakso et al 2000) have been found.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, reduction in the expression of endogenous BDNF has been shown to potentiate seizures induced by hippocampal kindling (Reibel et al 2000). The current work thus raises the possibility that reductions in hippocampal BDNF mRNA induced by uncondititioned stress or by re-exposure to cues previously paired with stress may be involved in the pathophysiology of hippocampus-dependent memory disturbances or decreases in hippocampal volume observed in stress-sensitive psychiatric disorders such as PTSD (Bremner et al 1995;Stein et al 1997;Gurvits et al 1996;Bremner et al 1997) and depression (Mervaala et al 2000;Vakili et al 2000). This also raises the possibility that unconditioned or psychological stress may facilitate the progression of dementing disorders such as Alzheimer's disease in which decreases in hippocampal BDNF levels (Hock et al 2000) and hippocampal volume (Laakso et al 2000) have been found.…”
Section: Discussionmentioning
confidence: 67%
“…Exposure to physical stress, such as immobilization, downregulates BDNF expression in the hippocampus (Smith et al 1995, Vaidya et al 1997 (Duman et al , 2000. Moreover, downregulation of BDNF could contribute to the hippocampal pathology observed in psychiatric disorders such as post-traumatic stress disorder (PTSD) and depression (Bremner et al 2000;Mervaala et al 2000;Vakili et al 2000). This possibility is supported by the observation that these disorders are sensitive to stressful experiences (Breslau et al 1995;Kendler et al 2000).…”
Section: This Study Examined the Effects Of Footshock Stress And Reexmentioning
confidence: 99%
“…5 Neuroimaging studies have produced a substantial body of knowledge about alterations of the limbic system in mood disorders. In the amygdala, alterations in cerebral blood flow and metabolism, 6 asymmetry of amygdalar volumes, 7 as well as smaller [8][9][10] and larger volumes [11][12][13][14] have been observed in depressed subjects when compared with normal controls. In the hippocampus, volumetric analysis studies have also revealed reduced volumes in subjects suffering from major depression in some, 7,11,[14][15][16][17][18][19][20] but not all studies 10,[21][22][23] comparing depressed patients versus controls.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, depression may be considered a consequence of stress-induced impairment in the plasticity of several brain areas (Duman, 2002). In particular, the hippocampus, a region critically involved in motivation and emotion processing (Eichenbaum and Otto, 1992), has been shown affected in depressed patients (Bremner et al, 2000;Mervaala et al, 2002;Sheline et al, 2000) and in animals exposed to experimental models of depression (Watanabe et al, 1992;Magariños et al, 1996). Dysfunction of neuronal plasticity could therefore contribute to the pathophysiology of mood disorders and recovery could occur by induction of the appropriate plasticity or remodeling phenomena (Akhondzadeh, 1999;Duman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several magnetic resonance imaging (MRI) studies of patients with major depression have described a diminution of hippocampal volume (Bremner et al, 2000;Mervaala et al, 2002;Sheline et al, 2000). In addition, some phenomena possibly related to this volume diminution have been reported in preclinical studies that employ stress exposure as a predisposing factor to depression: shrinkage of the apical tree of hippocampal CA3 pyramidal neurons (Watanabe et al, 1992;Magariños et al, 1996), alterations in axonal components, downregulation of neurogenesis in the subgranular layer of the adult dentate gyrus and putative glial changes (Czéh and Lucassen, 2007).…”
Section: Introductionmentioning
confidence: 99%